Technological Innovation in Architectural Design Education: Empirical Analysis and Future Directions of Midjourney Intelligent Drawing Software - Chong Xu; Yi Huang (Buildings)
This study investigates the role of Midjourney intelligent drawing software in architectural design education, particularly its impact on design efficiency and creativity among sophomore architecture students. While Midjourney serves as a powerful tool for rapid visual concept generation, it does not replace traditional design skills but complements them by enhancing the visualization process. The study also identifies some key limitations of Midjourney, especially in areas of functionality and sustainable design, which require students to integrate additional tools for a more comprehensive design approach. The recommendation to expand the use of intelligent drawing technologies like Midjourney in future research is supported by the observed improvements in student performance, including enhanced creative expression and efficiency in design processes. These conclusions are based on qualitative data derived from student feedback, as well as quantitative measurements of their design outcomes before and after using the software. Furthermore, it highlights the need to broaden the scope of studies to include a wider variety of educational contexts and source materials to improve understanding of the software’s potential in design education.